Experimentalismo, iluminismo e fisiocratismo na obra de um cirurgião moderno : evocando Lima Bezerra (1727-1806) - Tavares, Pedro Vilas Boas (2013)
The article analyses the life and work of Manuel Gomes de Lima Bezerra (1727-1806), a surgeon from Ponte do Lima: he was not only pioneer in the use of new methods and instruments in medical education — and thereby equally in public health —, but he was also a pioneer in the different fields of knowledge (particularly those which affected the needs of the population of the Entre-Douro- -e-Minho region) with which, as a man of science, he was familiar.